Diversity and distribution of seagrasses in the Union of the Comoros. Issue 2 (19th August 2016) - Poonian, CNS; Tuharska, K; Hauzer, MD
Abstract : This study represents the first in situ assessment of seagrasses in the Union of the Comoros. The presence of the following 10 species (ranked in order of abundance) was confirmed: Thalassia hemprichii, Thalassodendron ciliatum, Syringodium isoetifolium, Halodule wrightii, Cymodocea rotundata, Cymodocea serrulata, Halodule uninervis, Halophila ovalis, Zostera capensis and Enhalus acoroides . Seagrasses occurred in large, continuous beds in the shallow waters at the northern and southern tips of Grande Comore Island and around the Bimbini Peninsula on western Anjouan Island, but were sparsely distributed throughout the shallow waters surrounding Mohéli Island.